Seychelles Tourism Sector Review : Sustaining Growth in a Successful Tourism Destination - World Bank (Washington, DC, 2014)
The Seychelles tourism sector today is a success story. No doubt, the Seychelles has been endowed with wonderful natural tourism assets in its beautiful beaches and mountain backdrops, but its success has also been due to good governance and strategic policy choices. With 24.8 percent of gross domestic product (GDP) directly attributable to tourism, the Seychelles must ensure that its tourism sector will continue to be competitive in the long-run. In that context, it will need to make difficult but critical choices about where the sector should be headed and how it should work towards that vision. This review of the Seychelles tourism sector has been conducted as part of a larger Indian ocean regional tourism integration study including similar reports on Mauritius, Comoros, and Madagascar. Each of these provides a brief sector overview that incorporates an up-to-date analysis of the country's tourism performance, highlights some of the sector's key challenges, and provides a select set of recommendations for addressing such challenges. The four sector reviews serve as a foundation for a synthesis policy note that addresses tourism at the regional level. This report is structured as follows: section one gives introduction to the Seychelles study; section two gives overview of the Seychelles tourism sector; section three presents key issues; section four gives recommendations; and section five gives conclusion.